Desenvolvimento de um aparato experimental para determinação da velocidade de uma bolha de gás escoando em líquido estagnado - Ando, André Vinícius Segall (2021)
Multiphase flows have been studied for many decades, due to their applications in industry sectors, such as in petroleum activities, in the nuclear energy sector, in refrigeration cycles, among others. The study of an elongated gas bubble flowing in stagnant liquid inside pipes is of great importance for the analysis and understanding of multiphase flow models. Much of the knowledge about flow patterns has been obtained empirically, which makes evident the importance of studying and improving experimental methods related to the theme. This work aims to carry out the design and construction of an experimental apparatus for visualizing and determining the velocity of a gas bubble flowing in stagnant liquid, based on other works in the literature. The apparatus consists of a structure of aluminum profiles and acrylic tubes, which are fixed by means of clamps, as well as ball valves, among other materials. Through this apparatus, it is possible to verify the influence of the diameter and the inclination of the pipe, as well as the liquid viscosity, in the ascension velocity of a gas bubble. The gas bubble velocity was determined by processing videos recorded in the testing section of the apparatus and showed satisfactory agreement with the literature. The apparatus proves to be functional, simple to build, low cost, easy to operate and capable of adaptations and improvements.